Ebook contracts critical terms and lessons learned from both sides of the table - Bush, Cali.; Safari eBooks; TOC Conference (Tools of change for publishing) (2010 : New York, N.Y.) ([Calif.?] : O'Reilly Media, 2010)
"The real battleground for "Digital Rights Management" may turn out to be negotiating and managing contracts for selling digital content. Hear lessons learned from dozens of ebook and digital contracts (on both sides of the table). How are business terms evolving to handle emerging digital and mobile markets? Are there terms in your digital contracts that are holdovers from the print world and aren't in tune with the realities of digital markets? Learn about five key contract terms that should be in every ebook contract you sign, along with other "gotchas" learned from the trenches"--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher.
Description from resource description page (viewed Sept. 1, 2010).
Keywords: Publishers and publishing -- Congresses; Publishers and publishing -- Management; Electronic books; Contracts -- Interpretation and construction; Electronic books